Analisis aspek pasar dan pemasaran studi kelayakan bisnis BMT UGT Nusantara Cabang Pembantu Dampit - Rohimah, Wasilatur (Maliki Interdisciplinary Journal, 2024)
The aim of this research is to analyze the feasibility of market and marketing aspects at BMT Ugt Nusantara Capem Dampit. This research method uses qualitative methods with observation and documentation studies. The results of this research show that BMT Ugt Nusantara Capem Dampit is feasible in terms of market and marketing aspects.